Adult Burn Contracture Reconstructions Caused by Burn Injury During Childhood: Patients’ Quality of Life and Surgical Challenges - I Nyoman Putu Riasa; Bertha Kawilarang (Jurnal Plastik Rekonstruksi, 2026)
Introduction: In many low- and middle-income countries (LMICs), childhood burns continue to be common, and contractures that persist into adulthood lead to significant disability. Observational studies suggest that health-related quality of life (HRQoL) generally improves over time in adult burn survivors; however, individuals with burn-scar contractures experience greater disability and lower HRQoL.Method: Descriptive, single-centre case series. Four adults with longstanding contractures from childhood flame burns were identified: postoperative qualitative HRQoL data (unstructured interviews). Surgical techniques and outcomes were recorded from clinical notes and photographs.Results: Growth through the scar caused multilevel deformities (bone/joint, tendon, soft tissue). Staged surgery included: (i) wrist/hand contracture release with ligament stabilisation, K-wire fixation, and tendon lengthening; (ii) multistage auricular reconstruction using a costal-cartilage framework covered by a pedicled temporoparietal fascial flap (TPFF) and ultrathin scalp skin graft; (iii) trunk/inguinoperineal release with abdominoplasty-style umbilical and nipple-areola complex (NAC) repositioning, and pedicled latissimus dorsi myocutaneous (LD-MC) flap; and (iv) staged regional reconstruction following oncologic resection of squamous-cell carcinoma (SCC) arising in a burn scar. In all cases, daily function and psychosocial well-being improved, and patients returned to work, demonstrating strong motivation for staged procedures.Conclusion: Even when reconstruction is delayed until adulthood, focusing on high-impact functional goals in a staged plan produces meaningful HRQoL improvements for survivors of childhood flame burns in resource-constrained settings.